Gazing at the partner in musical trios: a mobile eye-tracking study - Sarah Vandemoortele; Kurt Feyaerts; Mark Reybrouck; Geert De Bièvre; Geert Brône; Thomas De Baets (Bern Open Publishing, 2018)
Few investigations into the nonverbal communication in ensemble playing have focused on gaze behaviour up to now. In this study, the gaze behaviour of musicians playing in trios was recorded using the recently developed technique of mobile eye-tracking. Four trios (clarinet, violin, piano) were recorded while rehearsing and while playing several runs through the same musical fragment. The current article reports on an initial exploration of the data in which we describe how often gazing at the partner occurred. On the one hand, we aim to identify possible contrasting cases. On the other, we look for tendencies across the run-throughs. We discuss the quantified gaze behaviour in relation to the existing literature and the current research design.